La question du « réel et son double » dans les créations théâtrales au secondaire - Hamel, Monique (Theatre Research in Canada / Recherches théâtrales au Canada, 2018)
In this article, Hamel examines the question of reality and its double in the context of theatrical creation at the high school level. The play and its public performance are seen as reality’s double and the character, that of its creator. Both doubles are apprehended, idealized, contested, opposed, and desired, as well as referential and autoreferential. How does the double emerge from creative work, and how is it significant in students’ educational and artistic experiences as well as their journey as spectators? Hamel’s study was carried out in the context of her doctoral work and is based on a content analysis of three theatrical creations (texts, scenarios, characters, stagings, and performances) as well as a series of semi-structured interviews with six students (now 32 to 36 years old, 16 to 20 years after the fact). What deeper significance did this creative experience have for these students as they prepared to enter adulthood? Hamel concludes that these learning experiences can have effects on the students’ very existence.